Distribution of extrafloral nectaries in different vegetation types of Amazonian Brazil - Morellato, L. P C; Oliveira, P. S. (My University, 1991)
Surveys were carried out in terra firme' forest, successional forest, buritirana' (palm vegetation) and shrub canga' (savanna). Extrafloral nectaries (EFNs) were present in 30 plant species belonging to 22 genera and 14 families. Nectary species represented 17.6-53.3% of the species samples in different areas, with local abundances varying from 19.1-50.0%. The percentage of species with EFNs was greater in the flora of the shrub canga than in the terra firme and successional forests. Nectary plants were more abundant in the shrub canga and successional forest. The high abundance of EFNs may be the result of intense foraging activity by ants on plants, leading to the formation of facultative mutualism. -from Authors
Keywords: ant; extrafloral nectary; forest; mutualism; palm; savanna; Brazil, Amazonia; South America, Amazonia